Tuning of work function of ZnO by doping and co-doping: an investigation using X-ray photoelectron spectroscopy - Soumya, K.; Selvam, I. Packia; Vinod, C. P.; Potty, S. N. (Thin Solid Films, 2022)
The shift in the work function of the ZnO thin film upon varying codoping ratio has been investigated by X-ray photoelectron spectroscopy. A notable shift of 0.2 eV in the work function was achieved in the films when the Al: In doping ratio was changed from 0:10 to 10:0. The elemental composition of the dopants obtained from XPS analysis showed the presence of more amount of In dopant than Al in codoped ZnO films. In this way a clear understanding of the variation in electrical properties on dopant ratio is obtained. A decrease in work function was also observed with the increase in free carrier concentration when the codopant ratio is changed. The effects of Burstein moss, band narrowing, and band renormalization observed in the bandgap were explained by an upward and downward shift of valence band maxima of the corresponding thin films. The controllable work function of the codoped ZnO films by varying the doping ratio offers excellent potential advantages in optoelectronic devices.
Keywords: Indium -Aluminum co -doping; Spray coating; thin film; Work function; X-ray photoelectron spectroscopy; Zinc oxide

Enhanced light-matter interaction in gas nitridation-derived TiNx thin films for potential plasmonic applications - Tony, Liya; Selvam, I. Packia; Vinod, C. P.; Potty, S. N. (Journal of Materials Science, 2025)
Titanium nitride is a substitute material exhibiting improved opto-electrical characteristics suitable for plasmonic purposes with adjustable attributes. In this study, we have embraced an innovative methodology for the fabrication of titanium nitride thin coatings via the nitridation of RF magnetron-sputtered titanium metallic films for surface plasmon resonance utilisation. The augmented electrical and optical features of TiN thin coatings prepared through the nitridation procedure are reported for the first time. The metallic coatings underwent gas nitridation at diverse temperatures within the range of 450-600 degrees C. The titanium nitride phase evolution in the coatings was corroborated by x-ray diffraction and x-ray photoelectron spectroscopy examinations. The dielectric function is deduced from reflection spectra through Drude-Lorentz model fitting, and the manifestation of surface plasmon excitation in the visible region was confirmed by correlating with carrier concentration assessments and by ensuring the required negative permittivity in the region. The red shift of screened plasma wavelength was observed with the nitridation temperature, and the same is varied in the wavelength range 400-700 nm. Ultimately, surface plasmons were excited in coatings with optimised thickness using Kretschmann configuration in wavelength interrogation mode.